2014
DOI: 10.1055/s-0033-1356093
|View full text |Cite
|
Sign up to set email alerts
|

Botulinumtoxin bei der Behandlung depressiver Störungen

Abstract: Recently published studies have shown a reduction of depressive symptoms after treatment of the glabellar frown lines with BTX injections. Further clinical studies in larger patient samples are necessary to prove the efficacy and safety of BTX injections used for the treatment of depressive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…These results confirm that the use of onabotulinumtoxinA in the comorbid patient group is an efficient alternative to treat both diseases as hitherto several times shown for the isolated conditions (i.e. [26,27,28] for depression, [29,30,31,32,33] for migraine) and confirmed through meta-analytic approach studying both conditions separately [6,7,8,9]. Interestingly, onabotulinumtoxinA seems to enfold a slightly different beneficial effect dependent on whether a patient shows just one or both diseases together.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These results confirm that the use of onabotulinumtoxinA in the comorbid patient group is an efficient alternative to treat both diseases as hitherto several times shown for the isolated conditions (i.e. [26,27,28] for depression, [29,30,31,32,33] for migraine) and confirmed through meta-analytic approach studying both conditions separately [6,7,8,9]. Interestingly, onabotulinumtoxinA seems to enfold a slightly different beneficial effect dependent on whether a patient shows just one or both diseases together.…”
Section: Discussionsupporting
confidence: 78%
“…In this case, using a standardized effect size would lead to the comparison of effects that from a rigorous point of view could not be compared. An approach similar to ours has been used in [6,7] and partly in [9,8]. Second, from a clinical perspective, the standardized effect size has a less intuitive interpretation, while score reduction in a scale can easily lead to a clearer evaluation of the effect of the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parahippocampal gyrus is part of the limbic area, and the limbic lobe and cerebellum are involved in emotion processing [2931], which plays an important role in depression [34, 35]. Recently, published studies have shown a reduction in depressive symptoms after BoNT-A injection into the glabellar region [20, 21, 36, 37]. In our study, BoNT-A injection induced abnormal spontaneous brain activity in the cerebellum (especially the posterior lobe) and parahippocampal gyrus in patients with botulism, suggesting that BoNT-A could modulate the activity of these brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hawlik et al (2014), the trial evidence does not confirm unequivocally the reported anti-depressive effect of Botox injections. Blinded, well-designed studies with larger patient cohorts might be necessary.…”
Section: Botox Applications As Anti-depressive Therapy: Psycho-ethicamentioning
confidence: 95%